Community Involvement in Bandung River Cleanup for Flood Control - Baehaqi, Ahmad; Alicia, Nadira Putri (Jurnal Pendidikan Teknik Bangunan, 2025)
Rapid urban growth worldwide, including in Indonesia, has led to serious environmental challenges, particularly the decline in river quality due to widespread pollution. This condition has turned vital waterways into “garbage dumps,” negatively affecting urban ecosystems, tourism development, and public safety. In Bandung, poor river and drainage systems worsen these problems, leading to frequent floods and economic losses. Addressing these challenges requires effective urban river management through comprehensive and collaborative efforts involving government, the private sector, and local communities. A case study design involved 46 community members and volunteers along the Cikapundung River from October to November 2023. Primary data was collected via structured questionnaires, supplemented by secondary data and field observations. Data analysis using Excel described community understanding and participation levels. Survey results showed high community understanding of river cleanliness urgency (71% strongly agreeing). Participation effectively raised awareness (73.9% strongly agreeing on significance), and participants reported high satisfaction (67.4% strongly agree) and motivation (80.4% strongly agree). Crucially, 73.95% of respondents linked cleanup efforts to flood risk reduction. These findings suggest community participation is a valuable model for environmental awareness and flood mitigation. The study concludes that sustained community engagement in urban river management is pivotal for environmental sustainability and effective flood mitigation.